The Effect of Operating Cash Flow, Capital Expenditure, and Earnings Quality on Firm Value - Keysya Rosalina; Purwatiningsih (International Journal of Economics, Business and Innovation Research, 2026)
This research aims to examine the influence of operating cash flow, capital expenditure, and earnings quality on the value of companies in the IDXQ30 index listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The type of this research is quantitative with an associative approach. Data collection techniques were carried out thru documentation by accessing annual reports and financial statements of companies listed in the IDXQ30 stock index on the Indonesia Stock Exchange for the period 2020–2024. The research instrument consists of secondary data observation sheets, which were analyzed using E-Views 12 software. The research population includes 52 companies in the IDXQ30 index, while the sample was determined thru purposive sampling, resulting in 15 companies with a total of 75 observation data points. The research results show that, simultaneously (F-test), operating cash flow, capital expenditure, and earnings quality have an impact on the company's value. Partially, operating cash flow affects the company's value, earnings quality affects the company's value, while capital expenditure does not affect the company's value.